Marketing wewnętrzny w firmach ubezpieczeniowych jako element kreowania trwałych relacji firma-klient - Makowska, Aleksandra (Wydawnictwo Media Press, 2008)
Insurance service is mainly based on client-agent relationship. Its optimal level may be acquired when the attention is focused on the insurance company staff. Therefore the principles of internal marketing, directly derived from the relationship marketing, should be effectively implemented.
Keywords: marketing wewnętrzny; relacja firma-klient; firmy ubezpieczeniowe; zarządzanie firmą; kształtowanie relacji firma-klient; internal marketing; company-customer relationship; insurance companies; company management; shaping the company-customer relationship